WEB DEVELOPMENT BASED ON SDLC CONCEPT APPROACH IN E-COMMERCE AT BASUKI JAYA PHARMACY - Tri Hidayat, Ahmad; Nugroho, Adityo; Saifullah, Shoffan (University of Technology Yogyakarta, 2020)
E-commerce is a very rapid development of trade in various fields, including pharmaceuticals. One process is the provision of prescription or non-prescription drugs from pharmacies. The management practice is still done manually, which involves the buying and selling process in person. Besides, processing and drug supplies are also done manually. These reasons make the process less effective and efficient, so it is necessary to develop an information system in buying and selling (e-commerce), improving performance, and reaching the target market. This system development uses the SDLC (System Development Live Cycle) concept and e-commerce, specifically in the pharmaceutical sector. This process is carried out from requirements to testing. The development is an e-commerce website that can help in the pharmacy's buying and selling process. Besides, the website is capable of connecting with customers. The system can integrate existing supplies into a pharmacy information system. The design of this system uses the programming languages PHP and MySQL. The results were tested using the Black Box method with the results that all processes and functions performed were carried out correctly. The developed website can be implemented in e-commerce at the pharmacy.